Hubungan Antara Aktivitas Fisik dengan Kecemasan pada Lansia di Panti Pucang Gading Semarang dan Panti Wening Wardoyo Ungaran - Afnan Septiana Putri; Iskim Luthfa; Aspihan Aspihan (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Background: One of the psychological problems often faced by the elderly, especially those living in nursing homes, is anxiety. Physical activity is one of the factors that plays a role in reducing anxiety. Compared to elderly people who are less active, those who are physically active usually experience lower levels of anxiety Method: This study used cross-sectional methodology and observational analytical design. Using the Slovin technique, 95 elderly residents of Panti Wening Wardoyo Ungaran and Panti Pucang Gading Semarang became the research sample. The Physical Activity Scale for the Elderly (PASE) questionnaire was used to measure physical activity, and the Beck Anxiety Inventory (BAI) was used to examine anxiety levels. The Gamma correlation test was used to analyze the data. Result: The research findings show that the majority of elderly people in this study do physical exercise regularly (48.4%) and experience mild anxiety (51.6%). With a p value of 0.027 (p< 0.05), the results of the correlation test indicate a strong relationship between anxiety levels and physical activity.Conclusion: There is a relationship between anxiety in elderly people and physical exercise.